IMPLANTATION CRITERIA OF ORGANIZATIONAL STRUCTURE FOR BIG AND SMALL FITNESS COMPANIES IN THE SOUTH ZONE AND THE WEST ZONE OF THE CITY OF RIO DE JANEIRO (Fiep Bulletin - online, 2015)
The growth number of people that practices physical activities, led to an increase in offered services at fitness centers, aiming at to take care of the necessities and to awake the interests of the customers. With all this change in the fitness market, the search for physical or legal people who in such a way gave the service, management and consultancy for such the growth of the establishments, with the objective to elaborate, to manage, and to implant the organizational structure. These professionals present in its great majority varied backgrounds, and basing on this fact, the intention of this research was to investigate, to describe and to analyze the criteria for the implantation of the organizational structure in medium and big fitness companies in the south zone and the west zone of the city of Rio de Janeiro. For the attainment of the data for this research, a structuralized interview was carried through, where a sequence of fixed questions with objective questions of open and closed characteristics were used, being applied with the author and with the manager of the fitness center. The results demonstrated diversified and coherent answers, however taking the criteria for the implantation to the organizational structure in simplified form, where it can be conclude, that the professionals interviewed had presented little clarity on the arguments of the answers in relation to the criteria of implantation of its effective structure, according to the Administrative Theories and the new organizational trends.
Keywords: Fitness; Management; Consultancy and Organizational Structure.